Influence of linear habitats in mammal activity: test of the travel lanes hypothesis - COELHO,L. H. L. (1999)
Mammal activity was monitored by a track-analysis method, in a 180 ha forest fragment. Three 1 km transects, each one with six tracking stations were established: one along a road side and one along a stream bank ("travel lanes") and one in the forest interior. Transects were monitored for six weeks through the months of September, October and beginning of November 1996. The activity of six morph-species of mammals was accessed, providing 251 records. Results of linear and non-linear habitats were compared, to test the "travel lanes" hypothesis, which predicts higher mammal activity in linear habitats. No statistical evidence supporting the hypothesis was found. The roadside transect showed the lowest mammal activity, whereas the stream side transect showed the highest activity, but most of the records obtained were due to only one species; records of other species were scarce. I conclude that the "travel lane concept" should not be applied to all kind of environments, and the generality of the hypothesis should be accepted with care.